Postpartum Uterine Infections in Cows: Diagnosis and Treatment - An Overview - Sharma, Akshay; Singh, Madhumeet; Sharma, Amit; Kumar, Pravesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Postpartum uterine infections result from uterine contamination with pathogens during parturition. Most of the pathogens are environmental contaminants that are gradually eliminated during the first 6 weeks postpartum. Vaginoscopy is considered to be more accurate than rectal palpation for diagnostic purpose. Transrectal ultrasonography is helpful for the diagnosis of clinical endometrits and pyometra. Subclinical endometritis (SCE) can be detected after three weeks postpartum with the help of endometrial cytology. Administration of PGF2α or intrauterine infusion of cephapirin is the treatment of choice for chronic endometritis but in case of SCE, results are inconsistent. Immunomodulators, ozone pearls or foam have also been used for treatment of postpartum uterine infections. Economic losses associated with uterine infections in dairy cattle are due to cost of diagnosis and treatment of the infection, associated milk reduction and reduced fertility.